PREHISTORIC MARITIME MIGRATION IN THE PACIFIC ISLANDS: AN HYPOTHESIS OF ENSO FORCING - Anderson A.; Chappell J.; Gagan M.; Grove R. (My University, 2006)
Long-distance human migration across the Pacific Ocean occurred during the late Holocene and originated almost entirely in the west. As prevailing tradewinds blow from the east, the mechanisms of prehistoric seafaring have been debated since the sixteenth century. Inadequacies in propositions of accidental or opportunistic drifting on occasional westerlies were exposed by early computer simulation. Experimental voyaging in large, fast, weatherly (windward-sailing) double-canoes, together with computer simulation incorporating canoe performance data and modern, averaged, wind conditions, has supported the traditional notion of intentional passage-making in a widely accepted hypothesis of upwind migration by strategic voyaging. The critical assumption that maritime technology and sailing conditions were effectively the same prehistorically as in the historical and modern records is, however, open to question. We propose here that maritime technology during the late-Holocene migrations did not permit windward sailing, and show that the episodic pattern of initial island colonization, which is disclosed in recent archaeological data, matches periods of reversal in wind direction toward westerlies, as inferred from the millennial-scale history of ENSO (El NiNo-Southern Oscillation).
Keywords: LATE HOLOCENE; PREHISTORIC SEAFARING; COLONIZATION PATTERN; REMOTE OCEANIA; ENSO (EL NINO-SOUTHERN OSCILLATION); WIND REVERSALS; PACIFIC; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен